Strategi Pendekatan Pelayanan Kontekstual Kepada Suku Bajo Penganut Kepercayaan Animisme Berdasarkan - Kiki Rutmana; Sabda Budiman (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
Indonesia is a country that has a very religious cultural tribe. This diversity can also be seen from the beliefs of the existing tribes. One of the existing beliefs is animism. The tribe that still has animist beliefs is the Bajo tribe in Gorontalo, North Sulawesi. Evangelistic services are urgently needed for the Bajo tribe. An effective service in reaching out to tribal communities that are thick with local beliefs and culture is contextual service. This paper is presented to explain the strategy of a contextual service approach to the Bajo tribe as adherents of animist beliefs. The author uses the method used in this study is a qualitative research method by conducting a literature study approach. The text on which the author used to build the foundation of the theory is Acts 17:16-34. From the results of the study of the text, the author found a contextual service approach strategy for the Bajo people, namely by knowing the local situation carefully, respecting the beliefs adopted by the local community, using reasoning as a common foothold, and utilizing the teachings and paradigms of the local community to convey the gospel.